Balancing development and conservation?: an assessment of livelihood and environmental outcomes of nontimber forest product trade in Asia, Africa, and Latin America - Kusters, K.; Achdiawan, R.; Belcher, B.; Ruíz Pérez, M. (2006)
This article addresses the question, to what extent and under which conditions nontimber forest product (NTFP) trade leads to both livelihood improvement and forest conservation. We based the analysis on a standardized expert-judgment assessment of the livelihood and environmental outcomes of 55 cases of NTFP trade from Asia, Africa, and Latin America. The results show that NTFP trade benefits several components of peoples' livelihoods, but may increase inequality between households. Involvement of women in the production-to-consumption system (PCS) tends to have a positive impact on intrahousehold equity. In 80% of the cases, the commercial production of NTFPs does not enable people to make financial investments to increase quality and quantity of production, limiting the potential for development. In our set of cases, commercial extraction from the wild, without further management, tends to lead to resource depletion. NTFP production systems are generally considered to have lower environmental values than natural forest, but do contribute positively to the environmental values in the landscape. We found that higher livelihood outcomes are associated with lower environmental outcomes and conclude that NTFP trade is not likely to reconcile development and conservation of natural forest.